A new thio-Schiff base fluorophore with copper ion sensing, DNA binding and nuclease activity - Vikneswaran, R.; Syafiq, M.S.; Eltayeb, N.E.; Kamaruddin, M.N.; Ramesh, Subramaniam; Yahya, Rosiyah (Elsevier, 2015)
Copper ion recognition and DNA interaction of a newly synthesized fluorescent Schiff base (HPyETSC) were investigated using UV-vis and fluorescent spectroscopy. Examination using these two techniques revealed that the detection of copper by HPyETSC is highly sensitive and selective, with a detection limit of 0.39 μm and the mode of interaction between HPyETSC and DNA is electrostatic, with a binding constant of 8.97 × 104 M-1. Furthermore, gel electrophoresis studies showed that HPyETSC exhibited nuclease activity through oxidative pathway.